Rewarded for RISC. - Savage, Neil (Communications of the ACM, 2018)
The article presents profiles of Association for Computing Machinery's Turing award recipients John Hennessy and David Patterson. According to the author, the Novel Prize of computing was given for their reduced instruction set computer (RISC) chip design. Some facts of their works are included.